Heat transfer distribution and flow characteristics in a channel with perforated-baffles - Eiamsa-ard, Smith; Sripattanapipat, Somchai; Saysroy, Anucha; Promvonge, Pongjet; Maruyama, Naoki; Hirota, Masafumi (My University, 2022)
The current paper reports the prediction of heat transfer performance of a channel with a modified perforated-baffle in a square wings (SW-PB) form. Numerical results include flow/temperature field, local heat transfer distribution, and thermal performance of a channel installed with the transverse solid baffle (TB), perforated-baffle (PB), and perforated-baffle with square wings (SW-PB). The simulation results demonstrated that TB brought a large recirculation flow, PB induced small recirculation and SW-PB produced several impinging jets as well as recirculation flows. Heat transfer rates given by PB were lower than those provided by TB and SW-PB by around 6.8% and 7.3%, respectively which were accompanied by lower friction losses by about 11.8% and 3.6%, respectively. Although, SW-PB gave higher heat transfer, the assessment of thermal performance factor (TPF) showed that the benefit from lower friction losses was more important. Under the same pumping power, TPFs assisted by SW-PB were higher than that assisted by PB and TB by 6.0% and 3.3%, respectively. The highest TPF of 1.2 was captured by SW-PB at Re = 9,000.
Keywords: Heat transfer enhancement; Multiple impinging jets; Perforated-baffle; Perforated-baffle with square wings; Transverse solid baffle